Leadership Strategies for Promoting Social Responsibility in Higher Education - Sengupta, Enakshi; Blessinger, Patrick; Mahoney, Craig (Innovations in higher education teaching and learning., 2020)
This book explores the theoretical underpinnings and interventions of CSR practised by universities across the globe and the role their leadership plays in promoting this. It provides international examples from the US, Africa, Europe and Asia, with implications and insights for university leadership, staff, and students.